Widening Participation in Higher Education Casting the Net Wide? - Hinton-Smith, T.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
This collection offers an authoritative, up-to-date commentary on the challenges facing higher education today across both the UK and internationally. The book charts the impact of global economic trends and recent policy developments for students, academics, providers and changing course provision.
Keywords: Educational sociology; Higher education; Educational sociology .; Education and sociology; Education and state; School management and organization; School administration; Sociology; Sociology of Education; Higher Education; Sociology of Education; Education Policy; Administration, Organization and Leadership; Sociology, general